Not just chairs and tables: the social value of the proposal by Maria Montessori - Gabriella Seveso (Universidade Federal de Santa Maria, 2018)
The contribution has a historical focus with attention to current affairs and deals with Montessori education, which has recently been at the centre of a lively debate in Italy and new experiments. It wants to show the remarkable ethical and social value present in the proposal of Maria Montessori: a value that is currently somewhat neglected at the level of popularization because the Montessori concept is reduced in some cases to an educational method (child-friendly furnishings, materials and methods, single teacher). For this reason, the author of the contribution analyzes the inaugural speech on the occasion of the opening of a Children's Home in 1907, written and pronounced by Maria Montessori, focusing on some themes. The first theme is that of spaces: the Discourse highlights how Montessori thought of the symbolic and social value of the homes of children and their importance for the recovery of situations of degradation and misery. The second theme is that of the professional profile of the teacher: the words of Montessori show how the teacher has an important social function and is the person who grows future citizens, encouraging critical awareness through a relationship based on autonomy. A reinterpretation of the Montessori work in this light also encourages us to review the proposals of other authors of our cultural history not as educational methods, although innovative and interesting, but also and above all in their social message. This perspective appears ever more urgent and necessary in our age, which is facing very serious problems concerning the conditions of childhood.